Analisis of the tender process for traditional general contracting in Sarawak Malaysia - Tsen, Soo Fui. (UNIMAS, 2006)
Traditional General Contracting is the most common type of contracting known in the Sarawak construction industry, as it has been the main form of contract procurement for quite sometime.As our industry is growing, the tender process itself for Traditional General Contracting has not gone through much improvement since then to suit the local necessity. This thesis investigates on the problems that could occur in every stage of the tender process and to see if there are rooms for improvement. The improvement is necessary so as to optimize the tender process to meet the objective of a construction contract. Interviews were conducted to the major players in the tender process for Traditional General Contracting. The data obtained from interviews was analyzed and summarized to propose a theoretical model of good practices in the tender process for Traditional General Contracting.